Knowing the honey bee : a multispecies ethnography : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University, Palmerston North, New Zealand - Luttrell, Jordan (Massey University, 2017)
Multispecies scholarship argues that the non-human has been relegated to the background of discussions about who and what inhabits and shapes the world. This thesis engages with this discussion as an experimental multispecies ethnography with honey bees in Manawatu, New Zealand. I aim to centre the honey bee in ethnography through engagement in the practice of fieldwork as well as the representation of the findings of this engagement. The honey bee is commonly known as an introduced, domesticated species, kept by humans in beehives in apiculture. This conceals the agency of the honey bee, rendering it passive, productive and compliant to the desires of humans, or in need of human intervention for survival. To view the agency of the bee I undertook embodied, performative ethnography, interviewing beekeepers and becoming one myself. My methodology, which was shaped by the bee, traced the networks that honey bees were enrolled in. Encounters were awkward, one-sided, and sometimes dangerous. The representation of honey bees demands an approach which attends to multiple, distinct accounts of honey bee worlds, because the bee is a lively agent, contributing to, experiencing, and communicating about the multiple networks in which it is engaged. As such, the findings of this thesis are presented in three accounts of encounters with honey bees. These accounts are distinct, capturing the honey bee in different networks, but are also distinct in their narrative styles, progressing from a description of honey networks in the spirit of Actor-Networks, to writing with honey bee narrator in poetry. Ethnographic representation is inevitably partial and an act of imagination. However, becoming sensitive to the ‘bee-ness’ of the bee; the waggle, hum and sting, and employing narrative inspired by the multisensory apiary, in other words, shaping representation with honey bees in mind, is an act of privileging honey bees in writing, and exploring what more can be said of, and with, the bee.
Keywords: Honeybee; Bee culture; Human-animal relationships; Ethnology; Manawatu; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Social anthropology/ethnography; Honey bee; Agency; Ethnography; Multispecies